Sustainable city logistics planning : methods and applications. - Awasthi, Anjali, 1976- (Management science : theory and applications, 2019)
"City logistics planning is vital to improve goods transport in urban areas. It involves consolidation and coordination of goods transport activities to reduce the negative impacts of freight transport on city residents and their environment. The book presents novel and innovative approaches in the area of sustainable city logistics planning and is composed of three volumes. The first volume addresses key problem areas related to city logistics assessment and evaluation, mobility management, vehicle routing, demand management, smart city solutions, sustainable supply chain management, risk management, intelligent transportation systems, delivery location optimization, electricity planning, and transit policy simulation. The second volume is dedicated to electric vehicle charging, stakeholder engagement, e-commerce deliveries, corporate social responsibility, urban freight data collection, dynamic project management, postal logistics, sustainable hub location, urban freight transport planning, and stakeholder mobilization. The third volume deals with truck route choice planning, empty container repositioning, logistics planning under disruption, dynamic risk sensitive sequential decision-making, parking revenue management, sustainable parcel delivery planning, and smart multi-purpose utility tunnels. A variety of methods based on systems modeling and simulation, optimization, and data mining are proposed. Survey studies, best practices, state of the art, and practical applications complement the presented theoretical approaches. The book will serve as a useful resource to academicians and practitioners working in the area"--